Personal exposure to aldehydes and potential health risks among schoolchildren in the city - Yen, Yu-Chuan; Ku, Chun-Hung; Yao, Tsung-Chieh; Tsai, Hui-Ju; Peng, Chiung-Yu; Chen, Yu-Cheng (Environmental science and pollution research international, 2023)
Schoolchildren are sensitive to airborne aldehyde exposures. The knowledge regarding inhalation exposure to aldehydes and the factors influencing exposure in schoolchildren is limited. This study aimed to assess the variability and potential health risks of exposure to aldehydes (including formaldehyde) in schoolchildren. The important factors affecting personal exposure to aldehydes were also explored. Forty schoolchildren were recruited from the urban and suburban areas of Taiwan for aldehyde samplings and questionnaire surveys. Personal and indoor home samples of aldehydes were collected simultaneously during warm and cold seasons. We also identified the potential variables associated with aldehyde exposure based on the participant’s responses to the questionnaires using mixed-effects models. The dominant three abundant aldehydes identified in personal exposure samples were formaldehyde (geometric mean, GM = 12.2 µg/m 3 ), acetaldehyde (GM = 5.53 µg/m 3 ), and hexaldehyde (GM = 8.79 µg/m 3 ), accounting for approximately 80% of the total selected aldehydes. Higher personal exposure to aldehydes was observed during the warm season. Moreover, the within-subject variance was predominant, accounting for 66.6 to > 99.9% of the total variance in exposure. Schoolchildren had a high probability of overexposure to formaldehyde and acrolein, which resulted in an incremental lifetime cancer risk of 1.59 × 10 −4 (95th percentile = 4.64 × 10 −4 ). Season, location, household refurbishment, and indoor ventilation variables were significantly associated with personal exposure to aldehydes. The results can improve our understanding of aldehyde exposure among schoolchildren to propose mitigation strategies. These findings may be applied to further epidemiological studies.